Zinc oxide/graphene oxide nanocomposites efficiently inhibited cadmium-induced hepatotoxicity via releasing Zn ions and up-regulating MRP1 expression - Yun Liu; Xue Wang; Bo Si; Tong Wang; Yun Wu; Ying Liu; Yemian Zhou; Haiyang Tong; Xinwei Zheng; An Xu (Environment International, 2022)
Environmental cadmium (Cd) pollution has been verified to associated with various hepatic diseases, as Cd has been classified as one of the TOP 20 Hazardous Substances and liver is the main target of Cd poisoning. However, to design efficient hepatic antidotes with excellent detoxification capacity and reveal their underlying mechanism(s) are still challenges in Cd detoxification. Herein, ZnO/GO nanocomposites with favorable biocompatibility was uncovered their advanced function against Cd-elicited liver damage at the in situ level in vivo by 9.4 T magnetic resonance imaging (MRI). To explore the cellular detoxification mechanism, ZnO/GO nanocomposites was found to effectively inhibit the cyto- and geno-toxicity of Cd with the maximum antagonistic efficiency to be approximately 90%. Mechanistically, ZnO/GO nanocomposites competitively inhibited the cellular Cd uptake through releasing Zn ions, and significantly promoted Cd excretion via targeting the efflux pump of multidrug resistance associated protein1 (MRP1), which was confirmed by mass spectra and immunohistochemical analysis in kidney, a main excretion organ of Cd. Our data provided a novel approach against Cd-elicited hepatotoxic responses by constructed ZnO/GO nanocomposites both in vitro and in vivo, which may have promising application in prevention and detoxification for Cd poisoning.